If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9-5x=-3x-9
We move all terms to the left:
-9-5x-(-3x-9)=0
We get rid of parentheses
-5x+3x+9-9=0
We add all the numbers together, and all the variables
-2x=0
x=0/-2
x=0
| -195+12x=2x+127 | | 50-50=10a | | 7-4/3x=23 | | 14=-8v+6(v+5) | | -6h+9=3h | | 155=12d+35 | | 135x-100=535 | | 7-7y=-11 | | 2(x-11)+x= | | -14+3x=-59 | | 12w+6=6(2w+1) | | 3x-2x+4x-2=-3x+14 | | 9j-18j+-19j+12j=16 | | 9x-83=37+3x | | -19.5=6.1+4v-4.8 | | 4q+3=17 | | 2y+5+y+4=8y-1 | | 3(x-1)+5=3x+6 | | 1.5^x=9 | | 4(x–3)+2x=2(3x+6) | | -(1+7x)-6(-7-x)=36* | | 3/4x-12=2x-6+4 | | -24=n-17 | | 5(2x-3)=9+4x | | 2x-3+6x-15=180* | | 0.8x+54.6=1.2x+4.6 | | N+5n*7=43 | | 8d-1/3(6-15d)=63 | | X+2/3=2x-4/3 | | w+15=8 | | -3(-4-x)=2x+7 | | 126=7(x-5) |